The adjective concordances on the tourism brochure “wildiaries Indonesia”: Corpus linguistics-based analysis - Amalia Ilmi Fitriyanti (Journal of Education, Social & Communication Studies, 2025)
The many benefits that can be obtained from the tourism industry have become a challenge for tourism actors to create tourist attractions. By using brochures as promotional media, it is possible that tourists, especially foreign tourists, will be interested in visiting these tourist attractions. To find out the linguistic form of a tourism brochure, linguistic research was carried out on one of the tourism brochures in Indonesia. By using corpus linguistics as a tool to obtain vocabulary and terminology in the tourism sector as well as the grammar and features of the words used in the brochure. The method used in this research is a qualitative method with an analysis process to obtain conclusions. The results of the research will show a sample of the accords in the brochure in the form of adjectives, along with their form and type.